UPAYA MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR KOMPETENSI DASAR MENERAPKAN CARA PERAWATAN SISTEM STARTER DENGAN PENERAPAN MEDIA PEMBELAJARAN BERBASIS ANDROID PADA PESERTA DIDIK KELAS XI TEKNIK KENDARAAN RINGAN OTOMOTIF - Dianto, Aris (Jurnal Analisis Pendidikan Sosial, 2025)
This study aims to: (1) determine the implementation of Android-Based Learning media implementation in an effort to increase student motivation in PKKR subjects at SMK Prakarya Internasional; (2) Knowing the implementation of Android-based learning media implementation in an effort to improve student achievement in PKKR subjects at SMK Prakarya Internasional. The subjects of this study were students of class XI TKRO at SMK Prakarya Internasional. This type of research is included in the CAR (Classroom Action Research) whose steps are as follows: 1) planning; 2) implementation; 3) observation and; 4) reflection. Retrieval of research data through observation, written tests, and questionnaires with research instruments in the form of: 1) observation sheets; 2) test questions and; 3) questionnaire sheet. Observations were made to measure the implementation of PKKR learning with Android-based learning media. Written tests were conducted to measure learning and student achievement. Questionnaires were given to determine student responses. The data analysis technique for the instrument of observation sheet and questionnaire sheet is using the percentage formula, for the test question instrument using the percentage formula. The results showed that the application of Android-based learning media. in learning Light Vehicle Electrical Maintenance can increase students' motivation and learning achievement. This is based on the acquisition of the average percentage of student achievement in the first cycle of 67.21 and the average student achievement in the second cycle of 71.73. The achievement of the first cycle of KKM is 52.17% and the second cycle of KKM is 82.61%. The results of the observation of student learning activities in the first cycle were 82% on the aspect of paying attention, 34% on the note-taking aspect, 13% on the questioning aspect, 21% on the aspect of answering questions, 43% on the aspect of expressing opinions, 17% on the aspect of discussing the material, and 78% on the aspect of independent learning. The results of the observation of student learning activities in cycle II were 95% on the aspect of paying attention, 56% on the aspect of taking notes, 43% on the aspect of asking questions, 34% on the aspect of answering questions, 52% on the aspect of expressing opinions, 34% on the aspect of discussing the material, and 86% on the aspect of independent learning. In addition, students gave a very positive response to the application of Audio Visual Learning media in Motor Starter learning. This is based on the percentage of the questionnaire results of 95.65% of students responding very positively and 4.35% of students responding positively.